Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The Effectiveness of Teachers’ Job Performance Assessment in the Schools of Al-Batinah North Governorate, Sultanate of Oman in Their Perspective Mr. Mohammed Salim Ali Al-Jahwari 2. A comparative study between the Higher Education Council system of 1993 and the universities system of 2019 in the Kingdom of Saudi Arabia Dr. Saud Ghassan Albeshir 3. The reality of school crises management in public schools in capital city of sana’a, Republic of Yemen Mrs. Amal Mahfoud Khaled Abdalwahab 4. Prophetic educational methods in addressing some manifestations of bullying among students as recognized by middle school teachers Mr. Ahmed Mohammed Al- Essi 5. The mediating role of positivity in the relationship between psychological immunity and emotional control among health sector workers in Erbil city Dr. Izaddin Ahmad Aziz, Mrs. Delan Abdullah Mahmood 6. Kindergarten teachers’ knowledge of the initial indicators of autism spectrum disorder Mrs. Frah Ekram Mukhtar, Dr. Salwa Mustafa Khishaim 7. The effectiveness of digital stimuli in improving attention among students with mental disabilities Mr. Osama Musa Althaghafi